Investigations into an overlooked early component of painful nociceptive withdrawal reflex responses in humans - Thorell, Oumie; Ydrefors, Johannes; Svantesson, Mats; Gerdle, Björn; Olausson, Håkan; Mahns, David A.; Nagi, Saad S. (Frontiers in Pain Research, 2023)
Introduction: The role of pain as a warning system necessitates a rapid transmission of information from the periphery for the execution of appropriate motor responses. The nociceptive withdrawal reflex (NWR) is a physiological response to protect the limb from a painful stimulus and is often considered an objective measure of spinal nociceptive excitability. The NWR is commonly defined by its latency in the presumed Aδ-fiber range consistent with the canonical view that “fast pain” is signaled by Aδ nociceptors. We recently demonstrated that human skin is equipped with ultrafast (Aβ range) nociceptors. Here, we investigated the short-latency component of the reflex and explored the relationship between reflex latency and pain perception. Methods: We revisited our earlier work on NWR measurements in which, following convention, only reflex responses in the presumed Aδ range were considered. In our current analysis, we expanded the time window to search for shorter latency responses and compared those with pain ratings. Results: In both cohorts, we found an abundance of recordings with short-latency reflex responses. In nearly 90% of successful recordings, only single reflex responses (not dual) were seen which allowed us to compare pain ratings based on reflex latencies. We found that shorter latency reflexes were just as painful as those in the conventional latency range. Discussion: We found a preponderance of short-latency painful reflex responses. Based on this finding, we suggest that short-latency responses must be considered in future studies. Whether these are signaled by the ultrafast nociceptors remains to be determined.